(untitled) (Indian Journal of Animal Production and Management, 2015)
Rearing of commercial broilers up to 3-4 months of age till they attain 4-5 kg body weight is common in backyard system in Mizoram. The study was conducted to compare the performance of broiler under Intensive and Backyard System of management, for which 300 commercial broilers were reared in three replicates (100 birds in one replicate) under Intensive System in the College farm and another 300 birds were reared at farmers level under Backyard System in 10 replicates (30 birds / farmers). Cost of production/kg broiler was significantly lower in intensive system (Rs.54.15 and Rs.63.26) compared to backyard system (Rs. 65.05 and Rs. 106.49) system of rearing both at the end of 6th and 13th week of age. It was observed that the gross margin in broiler rearing up 6 weeks of age was quite satisfactory in both intensive and backyard system, however rearing of broiler up to 13th weeks of age reduced the margin, especially under backyard system rearing in state of Mizoram, which might be due to poor growth, higher feed consumption and because of higher mortality rate as compared to intensive system of rearing.